PENINGKATAN KEMAMPUAN GURU DALAM MENGELOLA KELAS MELALUI SUPERVISI KLINIS DI SMAN 10 BENGKULU - Marulloh Marulloh Marulloh (Manajer Pendididikan, 2016)
This action reserach excecuted in three clycles to enhance teacher competence in the class manajerial of SMAN 10 Bengkulu. The subject of the research are eleven teachers. Data were analyzed descriptively. The research show the increasing of mean score of teacher competence in the class managerial at cycle I, II, and III in accordance are 77,28, 80,67, and 89,98. The research conclude, that clinical supervision can improve teacher competence in theclass manajerial.Keywords: clinical supervision ,class managements.